The Implementation of Inquiry Learning to Improve Students’ Oral Activities in Biology at Grade XI of SMA N 5 Surakarta in the Academic Year 2014/2015 - Rizky Paramitha Tri Kurniawati Putri; Murni Ramli; Nurmiyati Nurmiyati; Mahargono Mahargono (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The aim of this study is to determine whether inquiry learning can improve students’ oral activities in Biology at Grade of XI MIA 5 SMA N 5 Surakarta. This research was conducted in the academic year 2014/2015 as a three-cycles action research. The subjects of this study were of Grade XI MIA 5 SMA N 5 Surakarta, 33 students. Data was collected questionnaire, observation, interview, and documentation. The data was compiled in tables and graphs and then analyzed. Analysis of the data was qualitative analysis, which described the result of questionnaires, observations, and interviews during the implementation of the action. The validity of the data is checked by expert validators. As the results showed that the average achievement of students aspects of oral activities based on observations at the first cycle was 60, 98%; Cycle II 69; 51%, and in Cycle III was 79,73%. Target achievement of oral activities was 30% at the end of the cycle. The conclusions of this study is the use of inquiry learning can improve students’ oral activities in Biology at Grade XI MIA 5 of SMA N 5 Surakarta.Keywords: inquiry learning, oral activities, biology senior high school